ANALISIS HUBUNGAN KEPEMILIKAN INSIDER DENGAN FUND RETURN, FUND TURN OVER, DAN FUND TAX COST REKSA DANA SAHAM PERIODE 2010-2013 - Desy Natalia Sihotang; Wahyu Ario Pratomo (Departemen Ekonomi Pembangunan USU, 2015)
This research aims to test and analyze the relationship between insider ownership by fund return, fund turn over, and fund tax cost. The method of sampling uses purposive sampling. The sample of this research is that active mutual fund shares during the period 2010-2013.The analysis method in hypothesis testing is to use Ordinary Least Square method (OLS), Fixed Effect Model (FEM), and Random Effect Model (REM). The result of the analysis with Random Effect Model indicates that the fund return in the form of negative affect yields with insider ownership and the magnitude of the impotion of the tax load mutual funds (fund tax cost) are not significant positive with insider ownership.The result of analysis of this study also showed that negative effect of fund turn over significantly with insider ownerhip. And the relationhip between insider ownership with independent variables showed that correlation quite weak. The result of this research indicate that the R-Squared (R2) only 0,397 (39,7%).Keyword: insider ownership, return, turn over, fund tax cost, mutual funds